Pengaruh Kualitas Layanan terhadap Citra Perusahaan, Kepuasan, Komitmen dan Loyalitas Nasabah (Studi pada Nasabah Tabungan BritAma Bank Rakyat Indonesia (BRI) di Provinsi Sulawesi Tenggara) - Nasrul, Nasrul; Albabsji, Taher; Nimran, Umar; Kumadji, Srikandi (Universitas Brawijaya, Indonesia, 2011)
This study aimed to see the influence of service quality on corporate image, satisfaction, commitment and loyalty of customers of Bank Rakyat Indonesia in Southeast Sulawesi. Originality of this study is the addition of variables related to commitment customers are then connected with customer loyalty analysis approach in this research is descriptive statistical analysis and analysis of Structural Equation Modeling (SEM). Research results indicate that there are ten hypotheses received or significantly related, whereas no significant variable is the relationship of the customer satisfaction variable does not significantly influence veriabel commitment to customer.